Mineral in man and animal - Wolff, H.G., Dr med. vet (British Homeopathic Journal, 1986)
The effectiveness of Mineral, in the treatment of dogs is demonstrated on the basis of case histories and statistics for eighty-three cases. The results are of significance and suggest that trials in human medicine as well as further veterinary studies would be of value.